#TITLE_ALTERNATIVE# - KRISTIAWAN (NIM : 15112072), DIAN
Pawon Cave is one where the discovery of ancient skeleton. It also became a part of the Bandung Basin formation. Pawon Cave is located on Rajamandala Rock Formations and now, it is threated by limestone mining around this site. There is a possibility that limestone mining will collapse the wall of Pawon Cave. It is important to make a documentation about the current condition of Pawon Cave. The way to make a docamentation can be done by performing 3D modelling technique using Terrestrial Laser Scanner (TLS). The method used in this study consists of data acquisition process using pulse-based TLS to scan object and data processing with a target-based registration technique, filtering using fence technique, and a series of meshing process. The result of registration from scanning process is 816.325.309 points with an average registration error 0.002 m, while the noise from scanning process is removed through filtering processes. After registration and filtering process, point clouds is converted into a solid object through a series of meshing process. The principle of the meshing process is changing point clouds into a solid object by connecting between points to generate Triangulated Irregular Network (TIN). The surface area of Pawon Cave model is 11052.494 m2 and its volume is 7450.195 m3. The average size difference between the Pawon Cave model and the real object is 0.003 m, with the largest size difference is 0.004 m and the smallest difference is 0.001 m.